2021
DOI: 10.15195/v8.a13
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Grandparent Education on Grandchildren's Cognitive Development: The Role of Parental Cognitive Ability

Abstract: Stratification and Social Policy) at the Goethe University Frankfurt am Main. His research focuses on the formation and development of social inequality over the life course. He is particularly interested in the role of specific life events (e.g., childbirth) in this process as well as in social stratification in childhood and its determinants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Parents in MRCs have significantly lower educational levels, which is associated with worse developmental outcomes in children. Similar associations between low educational levels and poorer outcomes in children were found by several studies focusing on children from other ethnic backgrounds [ 24 , 25 , 26 , 27 ]. Moreover, exploring the mediating pathways explaining the differences in early childhood development between children from MRCs and the majority population aligns with previous research emphasising the importance of considering mediating mechanisms in analysing the relationship between poverty and children’s developmental outcomes [ 39 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Parents in MRCs have significantly lower educational levels, which is associated with worse developmental outcomes in children. Similar associations between low educational levels and poorer outcomes in children were found by several studies focusing on children from other ethnic backgrounds [ 24 , 25 , 26 , 27 ]. Moreover, exploring the mediating pathways explaining the differences in early childhood development between children from MRCs and the majority population aligns with previous research emphasising the importance of considering mediating mechanisms in analysing the relationship between poverty and children’s developmental outcomes [ 39 ].…”
Section: Discussionsupporting
confidence: 84%
“…We found that the educational level of parents from MRCs is significantly lower than that of the majority population and is associated with worse developmental outcomes in children. Several studies confirmed parental (or maternal) education to be associated with children’s early development or specific domains of development to a certain level [ 25 , 26 , 35 , 36 ]. Parental education, occupation and income are highly interrelated components of socioeconomic position [ 23 ], which might influence children’s developmental outcomes via different mechanisms [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is plausible if the treatment and mediator are temporally and mechanistically proximate to each other but is likely violated in other settings. For example, Klein & Kühhirt (2021) investigated the role of parental cognitive ability in mediating the effect of grandparents’ education on grandchildren’s cognitive ability. In this case, it is likely that some posttreatment variables, such as grandparents’ income and occupational status, are affected by the treatment (grandparents’ education) and affect both the mediator (parental cognitive ability) and the outcome (children’s cognitive ability).…”
Section: Causal Effect Mediationmentioning
confidence: 99%
“…Furthermore, I perceive the life course as a laboratory in which experiments can be run to assess how outcomes change. In doing so, this study joins a growing body of research emphasizing that even if interventions were never practically feasible, formulating sufficiently well-defined hypothetical interventions helps to define meaningful effects, clarifies identification assumptions, and guides the choice of pragmatic estimation approaches that closely relate to the assumptions about the data generating process (see e.g., Hernán, 2018;Klein and Kühhirt 2021;Kratz, Pettinger, and Grätz, 2022;Lundberg et al, 2021;Morgan and Winship, 2015).…”
Section: Introductionmentioning
confidence: 99%